Complete mitochondrial genome of the sea star Archaster typicus (Asteroidea: Archasteridae) - Quek, Zheng Bin Randolph (Mitochondrial DNA B Resour, 2019)
The complete mitochondrial genome of the widespread and common Indo-Pacific sea star Archaster typicus has been sequenced in this study. The mitogenome is 16,230 base pairs (bp) in length, with 13 protein coding genes (PCGs), 22 tRNAs and 2 rRNAs. Gene order of its PCGs and rRNAs matches those of nine other asteroid taxa included for comparison in this study, and it has a similar nucleotide composition of 33.08% A, 26.38% T, 25.53% C and 15.01% G nucleotides. Phylogenetic analyses place A. typicus as the sister group to Acanthaster spp., consistent with previous inferences.